The Digital Disruption in Over-The-Counter Drug Retailing - Kristina Kleinlercher (Marketing Review St.Gallen, 2017)
While technology has disrupted retail industries such as electronics or apparel, it has just started to transform the healthcare market. This paper sheds light on the digital disruption in retailing with over-the-counter drugs in Switzerland, different customer segments purchasing non-prescription drugs, and technology-enabled health services.
Keywords: 650